Angiography-Derived Fractional Flow Reserve in Coronary Assessment : Current Developments and Future Perspectives - Chow, Han Bing; Shirley Tan, Siang Ning; Lai, Wei Hong; Alan Fong, Yean Yip (Compuscript, 2023)
Coronary physiology assessment is an important factor in guiding myocardial revascularization. A growing body of research highlights the value of using fractional flow reserve, FFR and other pressure-based indicators for functional assessment of stable coronary stenoses. Invasive functional coronary assessment techniques have evolved from intracoronary wire-based to wire-free approaches as a result of technological advancements. In addition, several software programs on the market have been thoroughly investigated and validated against invasive FFR, and have shown good accuracy and correlation. However, use of FFR remains modest. Hence, this review provides an overview of angiography-based FFR solutions and compares their technologies. Additionally, a systematic scoping review was performed to understand the research landscape in wire-free coronary physiology assessment, to complement the narratives of existing FFR trials on wire-free FFR. Furthermore, future developments and strategies that could expand the use of wire-free computed coronary functional assessment in the Asia Pacific region are discussed.